Pengembangan Metodologi Pengajaran Funny SKL dan Tutorial Sebaya di MTs Negeri 10 Sleman - Busyroni Majid (Jurnal Pendidikan Madrasah, 2020)
This research aims to develop a Funny SKL teaching methodology and peer-to-peer tutorials with psychological factors as the target. It is undeniable that the average value acquisition in a madrasah is still one of the parameters to be said to be a superior madrasah in the academic field. Teachers in MTs Negeri 10 Sleman have fulfilled the standards and in accordance with his educational background. The challenges faced by teachers to achieve a high national exam score are still weak to the motivation of the students. Madrasah seeks to develop learning methods to eliminate the barriers that exist in the students. MTs Negeri 10 Sleman has developed two methods of learning; First, Funny (SKL) Competency standards graduates, namely SKL focusing methods applied with the Capita selecta problem, both development of learning methods with peer tutorials. The development of this learning method is the same as the development of Madrasah culture, which is the formation of a character madrasah, Madrasah competence and Madrasah literation. The development of this learning method can result in an increase in the average acquisition of the national exam scores of the year 2016/2017 lesson years 2018/2019 as many as 3.6 points, and above the national average value.